PENGARUH STRATEGI PEMBELAJARAN THINK PAIR SHARE DAN MOTIVASI TERHADAP HASIL BELAJAR EKONOMI SISWA SMA - Asia, Asia (Fakultas tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Palu, 2016)
This research aimed to: (1) test the difference between the learning outcomes of two instructional strategies: they were think pair share and direct instruction, (2) test the difference between the learning result of the students with low motivation and those with high motivation, and (3) test the interaction between the learning strategies and the motivation to achieve towards learning result. This research used factorial 2x2 version non-equivalent control group design. The subjects of the research were the eleventh grade social science students at SMA Negeri 3, SMA Negeri 4, and SMA Negeri 7 in the academic year 2013/2014. The subjects were determined through cluster random sampling. Data were collected through pre test, post test, and motivation to achieve instruments which were analyzed in inferential statistic by using variance analysis with the significance level of 0.05. The results of the research showed that (1) there was a difference between the groups of students who were given treatments with cooperative learning strategy of think pair share and direct instruction, (2) there was a difference in the learning result of the students who have high and low motivation, and (3) there was a significant interaction between learning strategy, motivation to achieve and learning result.